Influence of Temperature Gradients and Heat Source in a Combined Layer on Double Component-Magneto-Marangoni-Convection. (6th January 2023) - Manjunatha, N.; Sumithra, R.; Alessa, Nazek; Loganathan, K.; Selvamani, C.; Gyeltshen, Sonam
Abstract : The present paper has enormous applications including fields of crystal growth, material processing, spacecraft, underground spread of chemical contaminants, petroleum reservoirs, waste dispersal and fertilizer migration in saturated soil, alloy solidification, and many more. The importance of double-diffusive convection has been recognized in various engineering applications, and it has thoroughly been investigated theoretically. In the presence of a constant heat source/sink on both layers, the double component-magneto-Marangoni-convection in a composite layer is examined. Due to heat, this combined layer is enclosed by adiabatic boundaries and exposed to basic temperature gradients. For the system of ordinary differential equations, the thermal surface-tension-driven (Marangoni) number, which also happens to be the Eigenvalue, is solved in closed form. For basic temperature gradients, the eigenvalues, or thermal Marangoni numbers are determined in closed form for lower rigid and higher free boundaries with surface tension, depending on both temperature and concentration. The effect of several parameters on the eigenvalue against depth ratio was studied. It is observed that the inverted parabolic temperature gradient on double component magneto-Marangoni-convection in a combined layer is the most stable of the three temperature gradients and for larger values of depth ratios, all physical parameters are nominal for the porous region dominant combined system.